2014
DOI: 10.3906/tar-1311-113
|View full text |Cite
|
Sign up to set email alerts
|

Siberian elm responses to different culture conditions under short rotation forestry in Mediterranean areas

Abstract: This work explores the possibilities of biomass production, for energy purposes, of Siberian elm in Mediterranean areas, including marginal lands with poor soil and low water availability. To achieve this, the influence of soil type, planting density, and water availability on biomass production were analyzed after the first 3 years of the growing cycle in 2 different locations. Moreover, a method to estimate biomass production as a function of some morphological parameters of the trees, as well as the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Chloroplast genome sequenced; breeding efforts targeting resistance to Dutch Elm Disease and wood quality Santini et al, 2004;Geyer et al, 2007;Lamers and Khamzina, 2008;Perez et al, 2014;Zuo et al, 2017 Wild tobacco (Nicotiana glauca Graham)…”
Section: Woody Tree 5-19mentioning
confidence: 99%
“…Chloroplast genome sequenced; breeding efforts targeting resistance to Dutch Elm Disease and wood quality Santini et al, 2004;Geyer et al, 2007;Lamers and Khamzina, 2008;Perez et al, 2014;Zuo et al, 2017 Wild tobacco (Nicotiana glauca Graham)…”
Section: Woody Tree 5-19mentioning
confidence: 99%
“…Furthermore, trials with other potentially usable species have taken place in recent years, leading to differing results. In this regard, at a Mediterranean scale, there have been experimental trials with Ulmus pumila L. [73], Robinia pseudoacacia L. [74][75][76][77], hybrids of Salix spp. [78][79][80][81], Platanus × hispanica Mill.…”
Section: Short Rotation Forest Crops For the Production Of Biomass: The Populus Genusmentioning
confidence: 99%
“…All the studied taxa are well adapted to the experimental growing conditions, as demonstrated by the growth rates and survival (>95%). The size reached by the plants (i.e., D, H) and the annual biomass yielded in these field trials (mean annual increments of about 12-14 t ha −1 year −1 for 3-5 years rotations, and CAI up to 15-20 t ha −1 year −1 according to Figures 1-4) are lower than the highest mean biomass production (20-50 t ha −1 year −1 ) reported in the Iberian Peninsula with other woody crops, such as Eucalyptus, kenaf or Leucaena [11,12,30,59,71,72], but it is within the highest production range reported for the taxa studied [18][19][20]23,73,74]. However, under conditions of high water and nutrient availability, mean biomass yields of around 20 t ha −1 year −1 can be obtained with hybrid poplar clones [18,75,76].…”
Section: Plant Growth and Biomass Productionmentioning
confidence: 63%
“…Recent studies have shown that Robinia pseudoacacia, Ulmus pumila and Populus sp. stand out in areas under a Mediterranean continental climate with cold winters, in Central Europe and North America, as they can tolerate winter frosts well below -20 °C [19,[28][29][30][31]. The latter has a great capacity to adapt to different environmental conditions, as well as a high hybridization capacity and ease of vegetative propagation.…”
Section: Introductionmentioning
confidence: 99%